Dear Johhanes,

In your “A guide to specifying observation equations for estimation of DSGE models” page 58 footnote,

demeaned growth rates observation equation is:

ytobs=log(yt)- log(yt-1)

However, from equation 64 and equation 65,

it seems that ytobs= log(yt)- log(yt-1) + log(ut)- mean (log(yt)- log(yt-1) + log(ut))=log(yt)- log(yt-1) + log(ut)- constant Lamda, since mean (log(yt)- log(yt-1) + log(ut))=constant Lamda in equation 65. This is quite different from the footnote.

So I am wondering if I make any mistake?

Best regards,

Huan